Antona Czechowa spojrzenie na bieg historii - Andrzej Ksenicz (Studia Rossica Posnaniensia)
Among the issues, themes and contributions which Anton Chekhov undertook in his works, one may also find the broadly-understood issue of an individual's place in the course of historical events. In this case, and others like it, this writer's opinion stands out among the works of other Russian writers. This is related to the fact that the author of The Steppe is convinced that the individual, and his conscious behaviour, contributes to the behaviour of a group and society. This is in contrast to the reasoning of most Russian writers of those times; however, it proves to be characteristic of Chekhov's thinking.